(untitled) (Journal of Educational Sciences, 2018)
For the sustainable development of society and the realization of the goal of improving the quality of education, it becomes important to define and develop not only the state policy in the field of education, but also the school policy of the republic as a whole and of each secondary educational institution of the republic too. In this article, we examine the structure and generalize the types of school policy in Kazakhstan. The purpose of the article is to develop the structure of school policy and to generalize the experience of modern Kazakhstan schools in defining school policy, to offer recommendations for the development of school policy. School policy is defined in two levels of implementation and development: state school policy and the school policy of the institution. The school policy of the institution is determined by the state school policy and is changed in accordance with the specifics of the type of the particular school. The structure of the school policy is determined by the elements – personnel policy, academic and methodical policy, upbringing policy, distributive and resource policy. At the level of the state school policy, the “General strategies and priorities for the development of school education” are additionally set out. At the policy level of a particular school – “School traditions and strategies and directions for the development of a particular school”, taking into account the features of the school. In the article recommendations for the developmento of school policy of Kazakshan are offered. Key words: school policy, academic policy, school, personnel policy, academic and methodical policy, upbringing policy.